2017
DOI: 10.1002/pssa.201700500
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Highly Crystalline Covellite Copper Sulphide Thin Films by SILAR

Abstract: Thin films of the covellite phase of CuS are of special importance due to their properties for optoelectronic device applications. Their preparation by chemical solution methods could enable their deposition on flexible substrates at low temperature for large area applications. Successive Ionic Layer Adsorption and Reaction (SILAR) is a promising option because it is simple, inexpensive, and allows the control of thickness and composition. However, low crystalline CuS thin films have been reported so far. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the visible region, a relatively high transmission followed by an absorption edges can be observed, indicating typical semiconductor behavior. In addition, the fall down of transmitted light could be due to the forbidden band gap of CuS [25]. Figure 5 shows the optical transmittance spectrum of the CuS thin film measured at wavelengths ranging from 400 to 1200 nm.…”
Section: Cus Thin-film Compositional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the visible region, a relatively high transmission followed by an absorption edges can be observed, indicating typical semiconductor behavior. In addition, the fall down of transmitted light could be due to the forbidden band gap of CuS [25]. Figure 5 shows the optical transmittance spectrum of the CuS thin film measured at wavelengths ranging from 400 to 1200 nm.…”
Section: Cus Thin-film Compositional Propertiesmentioning
confidence: 99%
“…In the visible region, a relatively high transmission followed by an absorption edges can be observed, indicating typical semiconductor behavior. In addition, the fall down of transmitted light could be due to the forbidden band gap of CuS [25]. The band-gap energy (Eg) of the CuS thin film was calculated using the Tauc plot for absorption coefficient α obtained from the transmittance spectra, and the results are shown in Figure 6 [26].…”
Section: Cus Thin-film Compositional Propertiesmentioning
confidence: 99%
“…The mass of P-1, P-2, P-3 and P-4 is estimated as 0.23, 0.41, 0.66 and 0.51 mg cm −2 respectively. It is observed that, the deposited mass increased from 20 to 30 cycles and gets decreased from 30 to 35 cycles due to the overgrowth and subsequent collapsing of the film [39][40][41][42]. Meticulous monitoring of (3) the film thickness is important because an increase in the film thickness increases mass loading on the substrate which reduces the stress to the substrate, results in peeling off the overgrown mass [42].…”
Section: Resultsmentioning
confidence: 99%
“…The E g value for the ZnS sample is found to be 3.5 eV, corresponding to ZnS, 22,25 and with an increasing copper concentration in the cationic solution, the E g decreases up to 2.37 eV for the 1.67 mM Cu 2+ sample, the value explained by the direct energy band gap of CuS covellite. 21,22,28 Interestingly, we can observe that the 0.67 mM Cu 2+ sample slightly falls out of the trend that the other samples follow, and the sudden decrease in the E g may be due to a possible formation of a transition phase that forms between the ZnS and CuS covellite end points.…”
Section: Uv−vis−nir Transmittance and Reflectance Spectramentioning
confidence: 88%
“…Our proposal sheds light on a critical challenge—how to synthesize high-quality CuS thin films directly on glass substrates. Until now, achieving this objective has been notably difficult without resorting to the use of seed layers like CdS 21 or complex deposition techniques.…”
Section: Introductionmentioning
confidence: 99%